Adopting a ‘Whole Trust’ infection prevention approach to reduce MRSA bacteraemia rate - Cooper, Tracy; Yam, TatShing (International Journal of Infection Control, 2007)
Set against a background of rising methicillin-resistant S. aureus (MRSA) infection rates, poor public image and recent staff reorganisation, the infection control team at Southampton University Hospitals NHS Trust has rallied to facilitate change in the infection prevention perceptions and practices throughout the Trust, adopting a ‘Whole Trust’ approach. By encouraging and facilitating local ownership of infection prevention initiatives and addressing specific infection control issues in key areas, with senior leadership from the Director of Nursing and Trust Board the Trust’s MRSA bacteraemia rate has been successfully reduced.